Resting-state network connectivity changes in drug-naive Parkinson’s disease patients with probable REM sleep behavior disorder - De Micco, Rosa; Piramide, Noemi; Di Nardo, Federica; Siciliano, Mattia; Cirillo, Mario; Russo, Antonio; Silvestro, Marcello; Tedeschi, Gioacchino; Esposito, Fabrizio; Tessitore, Alessandro (Journal of Neural Transmission, 2023)
Epidemiological studies have shown that Parkinson’s disease (PD) patients with probable REM sleep behavior disorder (pRBD) present an increased risk of worse cognitive progression over the disease course. The aim of this study was to investigate, using resting-state functional MRI (RS-fMRI), the functional connectivity (FC) changes associated with the presence of pRBD in a cohort of newly diagnosed, drug-naive and cognitively unimpaired PD patients compared to healthy controls (HC). Fifty-six drug-naïve patients (25 PD-pRBD + and 31 PD-pRBD − ) and 23 HC underwent both RS-fMRI and clinical assessment. Single-subject and group-level independent component analysis was used to analyze intra- and inter-network FC differences within the major large-scale neurocognitive networks, namely the default mode (DMN), frontoparietal (FPN), salience (SN) and executive-control (ECN) networks. Widespread FC changes were found within the most relevant neurocognitive networks in PD patients compared to HC. Moreover, PD-pRBD + patients showed abnormal intrinsic FC within the DMN, ECN and SN compared to PD-pRBD − . Finally, PD-pRBD + patients showed functional decoupling between left and right FPN. In the present study, we revealed that FC changes within the most relevant neurocognitive networks are already detectable in early drug-naïve PD patients, even in the absence of clinical overt cognitive impairment. These changes are even more evident in PD patients with RBD, potentially leading to profound impairment in cognitive processing and cognitive/behavioral integration, as well as to fronto-striatal maladaptive compensatory mechanisms.